Integrative metabolomic and transcriptomic analyses reveal the mechanisms of Tibetan hulless barley grain coloration - Xu, Congping; Abbas, Hafiz Muhammad Khalid; Zhan, Chuansong; Huang, Yuxiao; Huang, Sishu; Yang, Haizhen; Wang, Yulin; Yuan, Hongjun; Luo, Jie; Zeng, Xingquan (Frontiers in Plant Science, 2022)
Cereal grains accumulate anthocyanin during developmental process. The anthocyanin content increases at grain filling stages to develop grain coloration in cereals. However, anthocyanin biosynthesis responsible for grain coloring and its regulatory mechanisms controlled by structural and functional genes remain unclear. Therefore, this study aimed to explore the global map of metabolic changes linked to grain coloration of Tibetan hulless barley (qingke) using an integrative metabolome and transcriptome approach. Grains from three colored qingke cultivars at different developmental stages were considered for molecular and metabolic investigations. A total of 120 differentially accumulated metabolites (DAMs) and 8,327 differentially expressed genes (DEGs) were filtered. DEGs were mainly enriched in the phenylpropanoid and flavonoid pathways. The transcript levels of anthocyanin biosynthesis genes (PAL, C4H, 4CL, CHS, FLS, F3H, F3’H, DFR, ANS, GT, OMT, and MAT) significantly upregulate in colored qingke compared to the non-colored variety. During grain development and maturation, the strong correlation of HvMYC2 expression with anthocyanin contents and anthocyanin biosynthesis genes suggested it as a critical gene in anthocyanin accumulation. Further results confirmed that HvMYC2 could be activated by HvMYB and be a positive regulator of UV-B and cold tolerance in qingke. In addition, verification based on enzymatic assays indicated that six key modifier enzymes could catalyze glycosylation, malonylation, and methylation of anthocyanins, thereby dissecting the major anthocyanin modification pathway in colored qingke. Overall, our study provides global insight into anthocyanin accumulation and the mechanism underlying grain coloration in qingke.